-7(2+2x)=-70

Simple and best practice solution for -7(2+2x)=-70 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(2+2x)=-70 equation:


Simplifying
-7(2 + 2x) = -70
(2 * -7 + 2x * -7) = -70
(-14 + -14x) = -70

Solving
-14 + -14x = -70

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '14' to each side of the equation.
-14 + 14 + -14x = -70 + 14

Combine like terms: -14 + 14 = 0
0 + -14x = -70 + 14
-14x = -70 + 14

Combine like terms: -70 + 14 = -56
-14x = -56

Divide each side by '-14'.
x = 4

Simplifying
x = 4

See similar equations:

| 4x+3(-2x-7)=-7 | | 7a+10a+7a+12a=360 | | -(9-5n)= | | -2(4+m)+6(m-3)=14 | | 4(5x-4)+10=-3 | | 20+8(11-q)=-12 | | 240=126-v | | 6x-12x+9=-27 | | -24-5x=-4(x+5) | | y=101.21x+0.0991 | | 2(3*-0.5+2)-2*-0.5=6*-0.5+5 | | 3(4j-3)8=-1+12j | | 12a+99a=3885 | | -11u-6=3u^2 | | 32-8p=-8(4p+2) | | 7+x=8x-2 | | -7-3v-10+3v=0 | | 5x+48=3x-36 | | 2(3*0.5+2)-2*0.5=6*0.5+5 | | 11x^2y^2=33x^2y | | 3(6s+12-10s-6)=0 | | 3(3n+4)=54+6x | | -5.2+9=-8 | | 22r+10-2= | | (x+7).3=33 | | 15-5x=-40 | | -5.8+9=-8 | | 2(3x+2)-2x=6x+5 | | X-45+45=540 | | .01x+.04y=-10 | | 5*x=-20 | | -6n+8=8-6n |

Equations solver categories